Application of copper-based nano enzyme in dual-mode detection of oxidation resistance of tea polyphenol

A copper-based nanozyme is used in a dual-mode detection method to efficiently and accurately measure EGCG in tea polyphenols, addressing the limitations of existing methods by combining UV absorption and photothermal techniques for rapid antioxidant capacity evaluation.

CN119223910APending Publication Date: 2024-12-31NINGBO UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411360251.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Current methods for evaluating the antioxidant capacity of tea polyphenols, particularly epigallocatechin gallate (EGCG), are time-consuming and require skilled operators, and there is a lack of a dual-mode detection method using copper-based nanozymes.

Method used

A dual-mode detection method using a copper-based nanozyme that involves UV absorption and photothermal measurement to determine the antioxidant capacity of tea polyphenols by measuring absorbance and temperature changes in response to different concentrations of EGCG.

Benefits of technology

The method is simple, efficient, and highly sensitive, allowing for accurate determination of EGCG content in tea samples, thereby assessing their antioxidant properties effectively.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119223910A_ABST
    Figure CN119223910A_ABST
Patent Text Reader

Abstract

Compared with the prior art, the application of the copper-based nano-enzyme to the dual-mode detection of the antioxidant capacity of the tea polyphenol has the beneficial effects that the provided copper-based nano-enzyme is simple to prepare, and an EGCG (epigallocatechin gallate) dual-mode detection method based on the copper-based nano-enzyme is simple, convenient, efficient and high in sensitivity; the method has important application value in the aspect of detecting the equivalent weight of EGCG in the tea leaves and further evaluating the natural antioxidant capacity of the EGCG.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of nanoenzyme analysis and detection, and specifically relates to the application of a copper-based nanoenzyme in dual-mode detection of antioxidant capacity of tea polyphenols. Background Art

[0002] There is a balance of reactive oxygen species (ROS) in the human body. When the concentration of reactive oxygen species (ROS) increases beyond normal levels, they will have harmful effects on cell components such as proteins, lipids and DNA, leading to many diseases, including cancer, diabetes, neurological diseases, atherosclerosis, hypertension, acute respiratory syndrome, asthma, etc. The oxidative stress caused by ROS will also disrupt the balance of the body's antioxidant defense system. It is generally believed that tea has many excellent physiological activities such as antioxidant, anti-tumor, radiation protection and anti-aging. Studying the effect of tea on the balance of the human antioxidant defense system requires accurate evaluation of the antioxidant properties of different teas. Therefore, it is of great significance to establish a simple and rapid detection method for evaluating antioxidant properties.

[0003] At present, researchers usually use high performance liquid chromatography (HPLC) and gas chromatography (GC) and other technologies to separate and identify antioxidant active substances, but such methods are time-consuming and require experienced operators. The more commonly used antioxidant capacity detection methods include peroxide value method, iron ion reduction antioxidant capacity assay (FRAP method), diphenyl picryl phenylhydrazine (DPPH) method, oxidative free radical absorption capacity assay (ORAC) method, ABTS [2,2'-azobis (3-ethylbenzothiazoline-6-sulfonic acid)] method, etc. These detection methods have different principles, different applicable antioxidant substances, and different results when measured by different methods. Nanozymes are nanomaterials with natural enzyme-like catalytic activity. Among them, some nanozymes can catalyze the color reaction of H2O2 and TMB by simulating the activity of natural enzymes. The color reaction involves the generation of multiple ROS, and the addition of antioxidant substances will affect the color reaction. Therefore, the researchers reported an antioxidant capacity detection method based on the colorimetric reaction of hydrogen peroxide (H2O2) and 3,3',5,5'-tetramethylbenzidine (TMB) catalyzed by nanozymes.

[0004] The antioxidant activity of tea can be attributed to the tea polyphenols it contains. Tea polyphenols is a general term for polyphenols in tea, including catechins, flavonoids and flavonols, among which catechins account for 60% to 80% of the total content. The content of each type of catechin is different, and epigallocatechin gallate (EGCG) is the most effective component of tea polyphenols, accounting for about 50% of the catechin content.

[0005] So far, the copper-based metal organic framework nanozyme provided by the present invention has not been reported, and the research on the dual-mode detection method for evaluating the antioxidant capacity of tea leaves using EGCG equivalent based on nanozymes has not been reported. Summary of the invention

[0006] The purpose of the present invention is to provide a nanozyme that can be used for detecting the antioxidant capacity of tea leaves, wherein the nanozyme has multiple types of enzyme properties, and at the same time provide a dual-mode detection method that can be used for evaluating the antioxidant capacity of tea leaves (EGCG equivalent) to solve the problems existing in the existing antioxidant capacity evaluation methods.

[0007] To achieve the above object, the present invention adopts the following technical solutions:

[0008] An application of a copper-based nanozyme in dual-mode detection of antioxidant capacity of tea polyphenols comprises the following steps:

[0009] A. Preparation of copper-based nanozyme materials;

[0010] B. Epigallocatechin gallate solutions of different concentrations were mixed with the copper-based nanozyme solution, and then added to a solution containing NaAc-HAc buffer solution, hydrogen peroxide, and 3,3',5,5'-tetramethylbenzidine. The UV absorption spectrum was measured using a UV-visible spectrometer, and the absorbance at 653 nm was recorded. 653 , and the absorbance A at 653 nm is obtained 653 Standard curve of relationship with epigallocatechin gallate concentration;

[0011] C. Mixing different concentrations of epigallocatechin gallate solutions with a copper-based nanozyme solution, and then adding the mixture to a solution containing a NaAc-HAc buffer solution, hydrogen peroxide, and 3,3',5,5'-tetramethylbenzidine. After irradiating the mixed solution with a laser for a certain period of time, measuring its temperature with an infrared thermal imager to obtain a standard curve of the relationship between temperature and epigallocatechin gallate concentration.

[0012] D. Mix the tea water extract with the copper-based nanozyme solution, then add it to a solution containing NaAc-HAc buffer solution, hydrogen peroxide and 3,3',5,5'-tetramethylbenzidine, measure its UV absorption spectrum with a UV-visible spectrometer, and record the absorbance A at 653nm 653 and compared with the standard curve obtained in step B to obtain the equivalent of epigallocatechin gallate in the tea water extract, and then calculate the equivalent of epigallocatechin gallate in the tea leaves. The value of epigallocatechin gallate equivalent is used to evaluate the antioxidant capacity of the tea leaves;

[0013] E. Mix the water extract of the tea leaves with the copper-based nanozyme solution, measure the temperature change by photothermal method, and compare it with the standard curve obtained in step C to obtain the equivalent of epigallocatechin gallate in the water extract of the tea leaves, and then calculate the equivalent of epigallocatechin gallate in the tea leaves. The value of epigallocatechin gallate equivalent is used to evaluate the antioxidant capacity of the tea leaves.

[0014] In some embodiments, in step A, the preparation of the copper-based nanozyme material comprises the following specific steps:

[0015] A1. Dissolve 0.05-0.15 mmol copper chloride and 0.02-0.04 mmol imidazole phenyl porphyrin in 5-6 mL dimethylformamide to prepare solution A, and dissolve 0.1-0.3 g polyvinyl pyrrolidone in a mixed solution of 5-6 mL dimethylformamide and 5-6 mL ethanol to prepare solution B. The volume ratio of solution B to solution A is 2.2-1.8:1. Then, mix solution A and solution B together and perform ultrasonic oscillation to obtain a mixed solution.

[0016] A2. The mixed solution obtained in step A1 was sealed in a polytetrafluoroethylene autoclave and maintained at 80 ° C for 16 hours, and then the reaction system was cooled to ambient temperature;

[0017] A3. Centrifuge the mixed solution obtained in step A2 three times, wash and dry it with ethanol to obtain a purple precipitate, which is then stored at room temperature to obtain a sheet-like copper-based nanozyme material.

[0018] In some embodiments, the specific operation of step A3 is: centrifuging the obtained mixed solution, washing it with ethanol 2 to 3 times, drying it at 60 to 80°C for 24 to 48 hours, and storing it at room temperature to obtain a sheet-like copper-based nanozyme material, and the centrifugation parameters are as follows: time is 10 to 15 minutes, and the rotation speed is 7000 to 9000 rpm.

[0019] In some embodiments, the specific operation of step B is as follows: add 3,3',5,5'-tetramethylbenzidine solution, hydrogen peroxide solution, NaAc-HAc buffer solution, copper-based nanozyme aqueous solution, epigallocatechin gallate solution, and deionized water to the sample tube to make the reaction system 2mL, and the concentrations of epigallocatechin gallate in the reaction system are 0μM, 5μM, 10μM, 15μM, 20μM, 30μM, 40μM, 60μM and 80μM, respectively; then mix the above solutions evenly, react at room temperature for 15 minutes, detect the ultraviolet-visible absorption spectrum of 500-800nm ​​using an ultraviolet-visible spectrophotometer, and record the absorbance at 653nm; use the concentration of epigallocatechin gallate in the reaction system as the horizontal coordinate and the absorbance at 653nm as the vertical coordinate to obtain a standard curve of the relationship between absorbance and epigallocatechin gallate concentration.

[0020] In some embodiments, the wavelength of the laser used in step C is 808 nm, and the power is 1 to 2 W. The specific operation of step C is as follows: 3,3',5,5'-tetramethylbenzidine solution, hydrogen peroxide solution, NaAc-HAc buffer solution, copper-based nanozyme aqueous solution, epigallocatechin gallate solution, and deionized water are added to the sample tube to make the reaction system 2 mL, and the concentrations of epigallocatechin gallate in the reaction system are 0 μM, 5 μM, 10 μM, 15 μM, 20 μM, 25 μM, 30 μM and 40 μM, respectively; then the above solutions are mixed evenly, reacted at room temperature for 15 minutes, and the reacted solution is illuminated by a laser for 10 minutes, and its infrared thermal imaging image is obtained by a thermal imager. The temperature presented by adding different concentrations of epigallocatechin gallate is different, thereby obtaining a standard curve of the relationship between temperature and epigallocatechin gallate concentration.

[0021] In some embodiments, the water extract of tea leaves in steps D and E is obtained by soaking tea leaves in water, the mass of the tea leaves is 0.05-0.15 g, and the volume of water is 90-110 mL.

[0022] In some embodiments, the specific operation of step D is as follows: add 3,3',5,5'-tetramethylbenzidine solution, hydrogen peroxide solution, NaAc-HAc buffer solution, copper-based nanozyme aqueous solution, tea water extract, and deionized water to the sample tube to make the reaction system 2mL; then mix the above solutions evenly, react at room temperature for 15 minutes, use a UV-visible spectrophotometer to detect the UV-visible absorption spectrum of 500-800nm, substitute the absorbance at 653nm into the standard curve obtained in step B, and obtain the concentration of epigallocatechin gallate in the 2mL test system. The equivalent of epigallocatechin gallate in the tea water extract is obtained by calculation, and then the equivalent of epigallocatechin gallate in the tea sample is obtained.

[0023] In some embodiments, the specific operation of step E is as follows: add 3,3',5,5'-tetramethylbenzidine solution, hydrogen peroxide solution, NaAc-HAc buffer solution, copper-based nanozyme aqueous solution, tea water extract, and deionized water to the sample tube to make the reaction system 2mL; then mix the above solutions evenly, react at room temperature for 15 minutes, and then irradiate with a laser for 10 minutes, and use an infrared thermal imager to detect the temperature change of epigallocatechin gallate after adding different concentrations. According to the standard curve of temperature corresponding to different concentrations of epigallocatechin gallate prepared in step C and the concentration of epigallocatechin gallate, the concentration of epigallocatechin gallate in the 2mL test system is obtained, and the equivalent of epigallocatechin gallate in the tea water extract is obtained by calculation, and then the equivalent of epigallocatechin gallate in the tea sample is obtained.

[0024] In some embodiments, the concentration of the hydrogen peroxide solution is 6 to 9 mM, and the concentration of the 3,3',5,5'-tetramethylbenzidine solution is 4 to 6 mM.

[0025] In some embodiments, the concentration of the copper-based nanozyme aqueous solution is 15-30 μg / mL, the concentration of the NaAc-HAc buffer solution is 9-11 mM, and the pH is 3.75-5.75.

[0026] Compared with the prior art, the beneficial effects of the present invention are: Cu-TIPP is simple to prepare, the EGCG detection method is simple and efficient, the sensitivity is high, and it can show a good application effect. Therefore, it has important application value for detecting how much EGCG equivalent is in tea and then judging its natural antioxidant property. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 : Molecular structure of timidazole phenylporphyrin (TIPP).

[0028] Figure 2 : Scanning electron microscope photo of Cu-TIPP material in Example 1.

[0029] Figure 3 : X-ray photoelectron spectrum of Cu-TIPP material in Example 1.

[0030] Figure 4 : Absorption spectrum of Cu-TIPP material catalyzing H2O2 oxidation of TMB.

[0031] Figure 5 : Electron spin resonance spectrum of related free radicals produced when Cu-TIPP material catalyzes H2O2.

[0032] Figure 6 : Absorption spectrum of EGCG concentration determined by colorimetric method based on Cu-TIPP material.

[0033] Figure 7 : Temperature-concentration standard curve of EGCG concentration measured by photothermal method based on Cu-TIPP material.

[0034] Figure 8 : Absorbance-concentration standard curve of EGCG concentration measured by colorimetry using Cu-TIPP material.

[0035] Fig. 9 : Selective investigation of EGCG detection by colorimetric method based on Cu-TIPP material.

[0036] Fig.10 : Selective investigation of EGCG detection by photothermal method based on Cu-TIPP material.

[0037] Fig.11 : Actual investigation diagram of EGCG detection based on the dual-mode detection method of Cu-TIPP material. DETAILED DESCRIPTION

[0038] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.

[0039] It should be noted that the endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.

[0040] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with commonly understood meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from the commonly understood meanings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods.

[0041] Firstly, a nano metal organic framework nanozyme (Cu-TIPP) with copper as metal salt is prepared. The nanoparticle is characterized in having a sheet structure with a sheet thickness of 15 to 25 nm.

[0042] The preparation method of the above-mentioned Cu-TIPP includes the following steps: 1) dissolving 0.1mmol copper chloride and 0.03mmol imidazole phenylporphyrin (TIPP) in 4mL dimethylformamide to prepare solution A, dissolving 0.2g polyvinyl pyrrolidone in a mixed solvent of 4mL dimethylformamide and 4mL ethanol to prepare solution B, and then mixing the two solutions together and ultrasonically vibrating for 20 minutes. The mixed solution is sealed in a polytetrafluoroethylene high-pressure reactor and maintained at 80°C for 16 hours, and then the reaction system is cooled to ambient temperature. Finally, centrifuge three times at 8000rmp and wash and dry with ethanol to obtain a purple precipitate, which is stored at room temperature to obtain a flaky Cu-TIPP material.

[0043] 2) Materials: 4 mg of the material was dissolved in 200 mL of ethanol to obtain 20 μg / mL Cu-TIPP material.

[0044] According to the above scheme, the molar ratio of the copper chloride to imidazole phenyl porphyrin (TIPP) is 10:3.

[0045] According to the above scheme, the volume ratio of solution A to solution B is 1:2.

[0046] According to the above scheme, the rotation speed of the centrifugal separation is 7000-9000 rpm, and the duration is 10-15 minutes.

[0047] Secondly, the present invention mainly introduces the application of copper-based nanozyme dual-mode sensing strategy in the detection of natural antioxidant properties of tea polyphenols, which is characterized in that the content of epigallocatechin gallate (EGCG) in tea is detected. The method for detecting epigallocatechin gallate (EGCG) comprises the following steps:

[0048] 1) Draw an absorbance-concentration curve: Add 200 μL 5 mM 3,3',5,5'-tetramethylbenzidine (TMB) solution, 200 μL 8 mM hydrogen peroxide solution (H2O2), 200 μL pH = 4 NaAc-HAc buffer solution, 400 μL 20 μg / mL Cu-TIPP aqueous solution, 0-80 μM epigallocatechin gallate (EGCG) solution, and deionized water were added to make the reaction system 2 mL (the concentrations of EGCG in the reaction system were 0, 5, 10, 15, 20, 30, 40, 60 and 80 μM, respectively); the above solutions were then mixed evenly, reacted at room temperature for 15 minutes, and then the UV-visible absorption spectrum of 500-800 nm was detected by a UV-visible spectrophotometer, and the absorbance at 653 nm was recorded; the concentration of EGCG in the reaction system was used as the horizontal coordinate, and the absorbance at 653 nm was used as the vertical coordinate to obtain an absorbance-concentration standard curve.

[0049] 2) Drawing a temperature-concentration curve: add 200 μL of 5 mM TMB solution, 200 μL of 8 mM H2O2 solution, 200 μL of pH = 4 NaAc-HAc buffer solution, 400 μL of 20 μg / mL Cu-TIPP aqueous solution, 0-80 μM EGCG solution, and deionized water to the sample tube to make the reaction system 2 mL (the concentrations of EGCG in the reaction system are 0, 5, 10, 15, 20, 25 and 30 μM, respectively); then mix the above solutions evenly, react at room temperature for 15 minutes, and then use a laser to illuminate the reacted solution for 10 minutes. Obtain its infrared thermal imaging image through a thermal imager. The temperatures presented by adding different concentrations of EGCG are different, thereby obtaining a temperature-concentration standard curve.

[0050] 3) Detect unknown concentration of EGCG by colorimetry: add 200 μL 5 mM TMB solution, 200 μL 8 mM H2O2 solution, 200 μL pH = 4 NaAc-HAc buffer solution, 400 μL 20 μg / mL Cu-TIPP aqueous solution, 200 μL tea water extract, and deionized water to the sample tube to make the reaction system 2 mL; then mix the above solutions evenly, react at room temperature for 15 minutes, use a UV-visible spectrophotometer to detect the UV-visible absorption spectrum of 500-800 nm, substitute the absorbance at 653 nm into the absorbance-concentration standard curve to obtain the concentration of EGCG in the reaction system, and calculate the concentration of unknown EGCG.

[0051] 4) Detection of unknown concentration of EGCG by photothermal method: add 200 μL 5mM TMB solution, 200 μL 8mM H2O2 solution, 200 μL pH=4 NaAc-HAc buffer solution, 400 μL 20 μg / mL Cu-TIPP aqueous solution, 200 μL tea water extract, and deionized water to the sample tube to make the reaction system 2mL; then mix the above solutions evenly, react at room temperature for 15 minutes, and then irradiate with laser for 10 minutes, use infrared thermal imager to detect the temperature change after adding different concentrations of EGCG, and obtain the concentration of EGCG in the reaction system according to the temperature-concentration standard curve, and calculate the concentration of unknown EGCG.

[0052] The technical effects of the present invention are described below in conjunction with specific embodiments.

[0053] Example 1

[0054] The preparation steps of the sheet-like copper-based nanozyme Cu-TIPP material are as follows:

[0055] 0.1mmol copper chloride and 0.03mmol imidazole phenyl porphyrin (TIPP) (ligand molecular structure as Figure 1 ) was dissolved in 4 mL of dimethylformamide to prepare solution A, 0.2 g of polyvinyl pyrrolidone was dissolved in a mixed solvent of 4 mL of dimethylformamide and 4 mL of ethanol to prepare solution B, and then the two solutions were mixed together and ultrasonically shaken for 20 minutes. The mixed solution was sealed in a polytetrafluoroethylene autoclave and kept at 80°C for 16 hours, and then the reaction system was cooled to ambient temperature. Finally, centrifuged three times at 8000 rpm and washed and dried with ethanol to obtain a purple precipitate, which was stored at room temperature to obtain a flaky Cu-TIPP material. The Cu-TIPP material was characterized by scanning electron microscopy as shown below. Figure 2 The valence state of the relevant elements in Cu-TIPP can be obtained by X-ray photoelectron spectroscopy ( Figure 3). 4 mg of the material was dissolved in 200 mL of ethanol to obtain 20 μg / mL Cu-TIPP material.

[0056] Example 2

[0057] The enzyme-like catalytic activity of the Cu-TIPP material was investigated by performing the following operations: 1) adding 400 μL of 20 μg / mL Cu-TIPP solution, 200 μL of NaAc-HAc buffer solution at pH = 4.0, 200 μL of 5 mM TMB solution, 200 μL of 8 mM H2O2 solution and deionized water to a sample tube to make the reaction system 2 mL to obtain solution A; adding 200 μL of pH = 4.0 buffer solution, 200 μL of 5 mM TMB solution, 200 μL of 8 mM H2O2 solution and deionized water to a sample tube to make the reaction system 2 mL to obtain solution B; reacting at 20° C. for 10 min, the absorption spectra of solutions A and B were detected at 500 to 800 by a UV-visible spectrophotometer (see Figure 4 ); ESR (electron spin resonance spectroscopy) was used to measure the free radicals generated during the reaction. Cu-TIPP and H2O2 were mixed and the amount of hydroxyl radicals generated in the mixed solution at 0, 5, 10, 15, and 20 min was measured respectively (see Figure 5 a), Mix Cu-TIPP and H2O2, and measure the generation of the mixed solution at 0, 5, 10, 15, and 20 min. 1 The amount of O2 (see Figure 5 b), Cu-TIPP and H2O2 were mixed, and the amount of superoxide radicals generated in the mixed solution at 0, 5, 10, 15, and 20 min was measured respectively (see Figure 5 c), from the signal intensity of the free radicals becoming stronger over time, it can be seen that a variety of free radicals are generated during the reaction, thus confirming that the Cu-TIPP material has catalytic activity for a variety of enzymes.

[0058] Example 3

[0059] The EGCG content was detected by colorimetry, and the steps are as follows:

[0060] Draw an absorbance-concentration curve: add 200 μL 5 mM TMB solution, 200 μL 8 mM H2O2 solution, 200 μL pH = 4 NaAc-HAc buffer solution, 400 μL 20 μg / mL Cu-TIPP solution, 0-100 μM EGCG solution, and deionized water to the sample tube to make the reaction system 2 mL (the concentrations of EGCG in the reaction system are 0, 5, 10, 15, 20, 30, 40, 60, and 80 μM, respectively), and obtain the following: Fig.10The above solution was then mixed evenly, reacted at room temperature for 15 minutes, and the UV-visible absorption spectrum at 500-800 nm was detected using a UV-visible spectrophotometer, and the absorbance at 653 nm was recorded. (See Figure 6 ) The concentration of EGCG in the reaction system was taken as the abscissa and the absorbance at 653 nm was taken as the ordinate to obtain the working curve equation; (see Figure 7 )

[0061] Example 4

[0062] The photothermal method was used to detect the EGCG content. The steps are as follows:

[0063] Drawing temperature-concentration image: add 200μL 5mM TMB solution, 200μL 8mM H2O2 solution, 200μL pH=4 NaAc-HAc buffer solution, 400μL 20μg / mL Cu-TIPP solution, 0-30μM EGCG solution, and deionized water to the sample tube to make the reaction system 2mL (the concentrations of EGCG in the reaction system are 0, 5, 10, 15, 20, 25, 30 and 40μM respectively); then mix the above solutions evenly, react at room temperature for 15min, and then use a laser to illuminate the solution after reaction for 10 minutes. After 10 minutes of illumination, use a thermal imager to obtain its infrared thermal image ( Fig.11 ), the temperature of the infrared thermal imaging images presented by adding different concentrations of EGCG is different, thus obtaining a temperature-concentration image. (See Figure 8 )

[0064] Example 5

[0065] The selectivity of the Cu-TIPP-based colorimetric method for EGCG detection was investigated as follows:

[0066] Add 200 μL of 5 mM TMB solution, 200 μL of 8 mM H2O2 solution, 200 μL of pH = 4 NaAc-HAc buffer solution, 400 μL of 20 μg / mL Cu-TIPP solution, 100 μM of different test solutions, and deionized water to the sample tube to make the reaction system 2 mL; then mix the above solutions evenly, react at room temperature for 10 minutes, measure the UV-visible absorption spectrum of each of the above solutions at 500-800 nm, and record the absorbance at 653 nm; use each solution in the detection system as the horizontal coordinate and the absorbance at 653 nm as the vertical coordinate to obtain the following: Figure 6The experimental results are shown in Figure 1. As can be seen from the figure, the absorbance after adding gallic acid is significantly lower than that of solutions without other salt solutions (a) and solutions with the same concentration of glucose (Glu), lactose (Lac), maltose (Mal), galactose (Gal), fructose (Fru), cysteine ​​(Cys), melamine (Mel), sodium chloride (NaCl), etc., indicating that Cu-TIPP has a strong selectivity for EGCG. (See Fig. 9 )

[0067] Example 6

[0068] The selectivity of Cu-TIPP-based photothermal method for EGCG detection was investigated in the following steps:

[0069] Add 200μL 5mM TMB solution, 200μL 8mM H2O2 solution, 200μL pH=4 NaAc-HAc buffer solution, 400μL 20μg / mL Cu-TIPP solution, 100μM different test solutions, and deionized water to the sample tube to make the reaction system 2mL; then mix the above solutions evenly, react at room temperature for 15 minutes, irradiate them with a laser for 10 minutes, and measure the temperature changes of the above solutions with an infrared thermal imager. In the presence of EGCG, the photothermal conversion rate of Cu~MOFs is greatly reduced. On the contrary, the temperature does not change significantly after adding glucose (Glu), lactose (Lac), maltose (Mal), galactose (Gal), fructose (Fru), cysteine ​​(Cys), melamine (Mel), and sodium chloride (NaCl) at the same concentration, which can also strongly prove the selectivity of Cu-TIPP for EGCG. (See Fig.10 )

[0070] Example 7

[0071] To detect the EGCG content in tea, the steps are as follows:

[0072] Determination of EGCG content in actual sample tea: We bought black tea and green tea from the supermarket. Weigh 0.1g and soak it in water at 100℃ for 5 minutes. Add 200μL 5mM TMB solution, 200μL 8mM H2O2 solution, 200μL pH=4 NaAc-HAc buffer solution, 400μL 20μg / mL Cu-TIPP solution, 30μL tea water extract, and deionized water to the sample tube to make the reaction system 2mL; then mix the above solutions evenly, react at room temperature for 15 minutes, use a UV-visible spectrophotometer to detect the UV-visible absorption spectrum of 500-800nm, substitute the absorbance at 653nm into the working curve equation, and obtain the concentration of EGCG in the reaction system. At the same time, the above solution can also be reacted at room temperature for 15 minutes, irradiated with a laser for 10 minutes, and the temperature change can be observed with an infrared thermal imager. The temperature-concentration curve is brought in to obtain the concentration of EGCG in the reaction system, thereby calculating the EGCG content. The equivalent content of EGCG in green tea calculated by colorimetry was 8.3%, and the equivalent content of EGCG in black tea was 1.7%; the equivalent content of EGCG in green tea calculated by photothermal method was 7.9%, and the equivalent content of EGCG in black tea was 1.1%.

[0073] The colorimetric results are shown in Table 1 below. The recovery rates of EGCG in green tea are 93.24% to 105.1%, and the recovery rates of EGCG in black tea are 91.73% to 104.3%. It can be seen that the recovery rates meet the requirements, thus verifying the reliability and practicality of this method. The photothermal results are shown in Table 2 below. The recovery rates of EGCG in green tea are 102.8% to 91.6%, and the recovery rates of EGCG in black tea are 101.6% to 93.8%. It can be seen that the recovery rates meet the requirements, thus verifying the reliability and practicality of this method.

[0074] Table 1: Colorimetric method for the detection of epigallocatechin gallate (EGCG) in tea

[0075]

[0076] Table 2: Detection of epigallocatechin gallate (EGCG) in tea by photothermal method

[0077]

[0078] It can be seen from the embodiments of the present invention that the copper-nanozyme is simple to prepare, the detection method of epigallocatechin gallate (EGCG) is simple, efficient, highly sensitive, and can show good application effects. Therefore, it has important application value for detecting the content of epigallocatechin gallate (EGCG) in tea and then judging its natural antioxidant properties.

[0079] Although the disclosure is disclosed as above, the protection scope of the disclosure is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the disclosure, and these changes and modifications will fall within the protection scope of the present invention.

Claims

1. An application of a copper-based nanozyme in dual-mode detection of antioxidant capacity of tea polyphenols, characterized in that: The following steps are involved: A. Preparation of copper-based nanozyme materials; B. Epigallocatechin gallate solutions of different concentrations were mixed with the copper-based nanozyme solution, and then added to a solution containing NaAc-HAc buffer solution, hydrogen peroxide, and 3,3',5,5'-tetramethylbenzidine. The UV absorption spectrum was measured using a UV-visible spectrometer, and the absorbance at 653 nm was recorded. 653 , and the absorbance A at 653 nm is obtained 653 Standard curve of relationship with epigallocatechin gallate concentration; C. Mixing different concentrations of epigallocatechin gallate solutions with a copper-based nanozyme solution, and then adding the mixture to a solution containing a NaAc-HAc buffer solution, hydrogen peroxide, and 3,3',5,5'-tetramethylbenzidine. After irradiating the mixed solution with a laser for a certain period of time, measuring its temperature with an infrared thermal imager to obtain a standard curve of the relationship between temperature and epigallocatechin gallate concentration. D. Mix the tea water extract with the copper-based nanozyme solution, then add it to a solution containing NaAc-HAc buffer solution, hydrogen peroxide and 3,3',5,5'-tetramethylbenzidine, measure its UV absorption spectrum with a UV-visible spectrometer, and record the absorbance A at 653nm 653 and compared with the standard curve obtained in step B to obtain the equivalent of epigallocatechin gallate in the tea water extract, and then calculate the equivalent of epigallocatechin gallate in the tea leaves. The value of epigallocatechin gallate equivalent is used to evaluate the antioxidant capacity of the tea leaves; E. Mix the water extract of the tea leaves with the copper-based nanozyme solution, measure the temperature change by photothermal method, and compare it with the standard curve obtained in step C to obtain the equivalent of epigallocatechin gallate in the water extract of the tea leaves, and then calculate the equivalent of epigallocatechin gallate in the tea leaves. The value of epigallocatechin gallate equivalent is used to evaluate the antioxidant capacity of the tea leaves.

2. The application of the copper-based nanozyme in dual-mode detection of antioxidant capacity of tea polyphenols according to claim 1, characterized in that: In step A, the preparation of the copper-based nanozyme material includes the following specific steps: A1. Dissolve 0.05-0.15 mmol copper chloride and 0.02-0.04 mmol imidazole phenyl porphyrin in 5-6 mL dimethylformamide to prepare solution A, and dissolve 0.1-0.3 g polyvinyl pyrrolidone in a mixed solution of 5-6 mL dimethylformamide and 5-6 mL ethanol to prepare solution B. The volume ratio of solution B to solution A is 2.2-1.8:

1. Then, mix solution A and solution B together and perform ultrasonic oscillation to obtain a mixed solution. A2. The mixed solution obtained in step A1 was sealed in a polytetrafluoroethylene autoclave and maintained at 80 ° C for 16 hours, and then the reaction system was cooled to ambient temperature; A3. Centrifuge the mixed solution obtained in step A2 three times, wash and dry it with ethanol to obtain a purple precipitate, which is then stored at room temperature to obtain a sheet-like copper-based nanozyme material.

3. The application of the copper-based nanozyme in dual-mode detection of antioxidant capacity of tea polyphenols according to claim 2, characterized in that: The specific operation of step A3 is: centrifuging the obtained mixed solution, washing it with ethanol 2 to 3 times, drying it at 60 to 80° C. for 24 to 48 hours, and storing it at room temperature to obtain a sheet-like copper-based nanozyme material, and the centrifugation parameters are as follows: time is 10 to 15 minutes, and the rotation speed is 7000 to 9000 rpm.

4. The use of the copper-based nanozyme in dual-mode detection of antioxidant capacity of tea polyphenols according to claim 1, characterized in that: The specific operation of step B is as follows: add 3,3',5,5'-tetramethylbenzidine solution, hydrogen peroxide solution, NaAc-HAc buffer solution, copper-based nanozyme aqueous solution, epigallocatechin gallate solution, and deionized water to a sample tube to make the reaction system 2mL, and the concentrations of epigallocatechin gallate in the reaction system are 0μM, 5μM, 10μM, 15μM, 20μM, 30μM, 40μM, 60μM and 80μM, respectively; then mix the above solutions evenly, react at room temperature for 15 minutes, detect the ultraviolet-visible absorption spectrum of 500-800nm ​​using an ultraviolet-visible spectrophotometer, and record the absorbance at 653nm; use the concentration of epigallocatechin gallate in the reaction system as the horizontal coordinate and the absorbance at 653nm as the vertical coordinate to obtain a standard curve of the relationship between absorbance and epigallocatechin gallate concentration.

5. The use of the copper-based nanozyme in dual-mode detection of antioxidant capacity of tea polyphenols according to claim 1, characterized in that: The wavelength of the laser used in step C is 808 nm, and the power is 1 to 2 W. The specific operation of step C is as follows: 3,3',5,5'-tetramethylbenzidine solution, hydrogen peroxide solution, NaAc-HAc buffer solution, copper-based nanozyme aqueous solution, epigallocatechin gallate solution, and deionized water are added to the sample tube to make the reaction system 2 mL, and the concentrations of epigallocatechin gallate in the reaction system are 0 μM, 5 μM, 10 μM, 15 μM, 20 μM, 25 μM, 30 μM and 40 μM, respectively; then the above solutions are mixed evenly, reacted at room temperature for 15 minutes, and the reacted solution is illuminated by a laser for 10 minutes, and its infrared thermal imaging image is obtained by a thermal imager. The temperature presented by adding different concentrations of epigallocatechin gallate is different, so as to obtain a standard curve of the relationship between temperature and epigallocatechin gallate concentration.

6. The use of the copper-based nanozyme in dual-mode detection of antioxidant capacity of tea polyphenols according to claim 1, characterized in that: The water extract of tea leaves in steps D and E is obtained by soaking tea leaves in water, the mass of the tea leaves is 0.05-0.15 g, and the volume of water is 90-110 mL.

7. The use of the copper-based nanozyme in dual-mode detection of antioxidant capacity of tea polyphenols according to claim 1, characterized in that: The specific operation of step D is as follows: add 3,3',5,5'-tetramethylbenzidine solution, hydrogen peroxide solution, NaAc-HAc buffer solution, copper-based nanoenzyme aqueous solution, tea water extract, and deionized water into a sample tube to make the reaction system 2mL; then mix the above solutions evenly, react at room temperature for 15 minutes, use a UV-visible spectrophotometer to detect the UV-visible absorption spectrum of 500-800nm, substitute the absorbance at 653nm into the standard curve obtained in step B, and obtain the concentration of epigallocatechin gallate in the 2mL test system. The equivalent of epigallocatechin gallate in the tea water extract is calculated, and then the equivalent of epigallocatechin gallate in the tea sample is obtained.

8. The use of the copper-based nanozyme in dual-mode detection of antioxidant capacity of tea polyphenols according to claim 1, characterized in that: The specific operation of step E is as follows: add 3,3',5,5'-tetramethylbenzidine solution, hydrogen peroxide solution, NaAc-HAc buffer solution, copper-based nanozyme aqueous solution, tea water extract, and deionized water into a sample tube to make the reaction system 2mL; then mix the above solutions evenly, react at room temperature for 15 minutes, and then irradiate with a laser for 10 minutes, and use an infrared thermal imager to detect the temperature change of epigallocatechin gallate after adding different concentrations, and according to the standard curve of temperature corresponding to different concentrations of epigallocatechin gallate and epigallocatechin gallate concentration obtained in step C, obtain the concentration of epigallocatechin gallate in the 2mL test system, calculate the equivalent of epigallocatechin gallate in the tea water extract, and then obtain the equivalent of epigallocatechin gallate in the tea sample.

9. The use of the copper-based nanozyme in dual-mode detection of antioxidant capacity of tea polyphenols according to any one of claims 4 to 8, characterized in that: The concentration of the hydrogen peroxide solution is 6 to 9 mM, and the concentration of the 3,3',5,5'-tetramethylbenzidine solution is 4 to 6 mM.

10. The use of the copper-based nanozyme according to any one of claims 4 to 8 in dual-mode detection of antioxidant capacity of tea polyphenols, characterized in that: The concentration of the copper-based nanozyme aqueous solution is 15-30 μg / mL, the concentration of the NaAc-HAc buffer solution is 9-11 mM, and the pH is 3.75-5.75.

Citation Information

Cited By

  • Osmium-ruthenium nano-enzyme as well as preparation method and application thereof

    CN120679525A

  • Preparation method of PFC-1-UiO-66 heterojunction nano-enzyme and application of PFC-1-UiO-66 heterojunction nano-enzyme in multi-mode detection of catechol

    CN120908372A